System Dynamics Simulation Model to Assess Level of National Unity and Integration : A Focus on the New Economic Policy in Malaysia - Yap, Yin (Universiti Malaysia Sarawak (UNIMAS), 2019)
Since the formation of Malaysia, the Government have implemented various programmes and economic policies including the affirmative action plans, such as the New Economic Policy 1970-1990 (NEP), Third Outline Perspective Plan 2001-2010 (OPP) and the Economic Transformation Programme 2010 (ETP) to spur Malaysia to become a high income nation. The recently launched the Transformasi Nasional 2050 or TN 50, an iniative to plan for the future of Malaysia in the period 2020 to 2050. However, all the models used by the Government are mental models and such models tend to be static and not interactions of the variables. As the problem of national building is both complex, dynamic and non-linear, there is no analytical solution. The reasonable approach is to construct a simulation model which incorporate the endogenous as well as the exogenous variables of the problem in functional way. The SD model using the combination of hard (economic variables) and soft variable (social capital) generated the socio-economic scenarios of Malaysia up to 2050. The present proto-typed simulation model is an attempt to deduce the effects of the implementation of the NEP and the subsequent policies in the restructuring of the society of Malaysia. The feedback from the social capital survey of ethnic communities have been used to judge the effects of NEP on the level of unity and national integration of the diverse ethnic groups in Malaysia. The simulation of the proto typed model shows that social capital have a significant impact on the educational attainments of the ethnic groups. It is the linking and bridging social capital which help the Other Bumiputera to have upward mobility. It does not provide the total understanding of the issues of unity and integration of Malaysia. The model can then compress the space and time of the problem to enable policy makers to generate scenarios based on different policy options and also to seek how development policies hold up in the future.